The international transfer of individual career capital: Exploring and developing a model of the underlying factors - Oleškevičiūtė, Emilija; Dickmann, Michael; Andresen, Maike; Parry, Emma (Emerald, 2022)
Purpose The purpose of this literature review is to critically analyze, synthesize and integrate the currently fragmented literature concerning the factors affecting the international transfer of individual career capital (CC). Design/methodology/approach This paper is a systematic literature review of the factors affecting the international transfer of individual CC from/for expatriates, repatriates and other employed highly skilled migrants and return migrants. The findings are classified based on the Social Chronology Framework (SCF) proposed by Gunz and Mayrhofer (2015). Findings This systematic literature review suggests that the international transfer of individual CC, which can be expressed both as (1) individual-level transfer across different organizations located in different countries as the direct use and application of CC and (2) individual knowing-how transfer to other individuals within organization, is affected by the individual, organizational and broader contextual-level factors that are bound by the aspect of time. The authors summarize the findings by presenting a model of the factors affecting the international transfer of individual CC. Originality/value The authors align the CC framework (Defillippi and Arthur, 1994) to the SCF (Gunz and Mayrhofer, 2018) by explaining the factors affecting the international transfer of individual CC that go beyond the qualities of CC, including the Being, Space and Time domains. Moreover, the authors critique the current focus on the international CC transfer in the present suggesting that future research should explore this phenomenon as a more dynamic process. Finally, the authors contribute to the literature on the global mobility of highly skilled employees' by highlighting gaps in the knowledge of the international transfer of CC and presenting a future research agenda.
Keywords: Repatriation; Expatriation; Global work; Knowing-how; Knowing-whom; Knowing-why; International transfer of career capital